An assessment of the impact of pharmacogenomics on health disparities: a systematic literature review. (November 2017) - Martin, Antony; Downing, Jennifer; Maden, Michelle; Fleeman, Nigel; Alfirevic, Ana; Haycox, Alan; Pirmohamed, Munir
This review assessed evidence of disparities in benefits of pharmacogenomics related to 'model performance' in subgroups of patients and studies which reported impact on health inequalities. 'Model performance' refers to the ability of algorithms including clinical, environmental and genetic information to guide treatment. A total of 4978 abstracts were screened by one reviewer and 30% (1494) were double screened by a second independent reviewer, after which data extraction was performed. Additional forward and backward citation searching of reference lists was conducted. Investigators independently double rated study quality and applicability of included studies. Only five individual studies were identified which met our inclusion criteria, but were contradictory in their conclusions. While three studies of genotype-guided dosing of warfarin reported that ethnic disparities in healthcare may widen, two other studies (one reporting on warfarin and reporting on clopidogrel) suggested that disparities in healthcare may reduce. There is a paucity of studies which evaluates the impact of pharmacogenomics on health disparities. Further work is required not only to evaluate health disparities between ethnic groups and countries but also within ethnic groups in the same country and solutions need to be identified to overcome these disparities.